Image sources in Ali Mahmoud Taha's poetry (Texas Journal of Multidisciplinary Studies, 2024)
The poetic image was not an innovation in the world of poetry. It has existed since poetry was known, and poetry is based on it. Therefore, it has received great attention from ancient and contemporary scholars and critics. The image is therefore a feature that any linguistic text must have. It is a basic element, not a secondary one. Rather, it is an artistic necessity without which the literary work loses its appeal and poetic value, because it is an integral part, in addition to being an important starting point in poetic renewal movements throughout the ages. The poetic image has received great attention from poets in the modern era, especially those influenced by the Romantic school. Among these poets is the poet Ali Mahmoud Taha, as this study dealt with the sources of the image in his poetry, and talked about the poetic image in Arabic poetry, the types of image in Ali Muhammad Taha’s poetry, and the sources of the image in his poetry, which varied and had many ways of forming it, including: Nature, which is divided into two sections: (Silent), which is represented in all aspects of nature, such as rivers, mountains, the sun, stars, planets, spring, autumn, etc. (Living aspects), which are represented by humans, birds, animals, etc. Environment: It includes the desert or rural environment, the urban environment, as well as the image of women, which was and still is the essence of Arabic literature, ancient and modern. As for the myth, the poet employed it in many of his poems and it opened up broad horizons for him in employing legendary events and characters and linking them to contemporary situations.